CONSTRUCTING NATIONAL MORALITY: A CRITICAL DISCOURSE ANALYSIS OF U.S POLICY SHIFTS TOWARD RUSSIA IN THE CONTEXT OF UNITED NATIONS GENERAL ASSEMBLY RESOLUTION ES-11/7 - Khan, Dwiki Rahman (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study explores the construction of national morality in the United States’ policy shift toward the Russia–Ukraine war, employing a Concurrent Triangulation Mixed Methods approach. The primary focus is to examine the ideological polemic between President Joe Biden and the Democratic Party and President-elect Donald Trump regarding the ongoing conflict in Ukraine. It investigates how national morality is constructed through official statements and diplomatic positions of the respective administrations. Many Democrats have expressed full support for Ukraine’s independence and consistently backed UN resolutions that emphasize Ukraine’s sovereignty and its freedom from the influence and territorial control of the Russian Federation. However, Ukraine, as an independent nation, must now face a different reality, as President Donald Trump seeks peace between both parties. This rapid shift has compelled the United States to alter its political stance due to the divergent political direction established by President Trump. This study will analyze how such a swift transformation occurred, particularly when the United States rejected the United Nations General Assembly ES 11/7, which identified Russia as the aggressor.